2020
DOI: 10.1021/acs.orglett.0c01268
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Echinomycin and Its Analogues

Abstract: The first total synthesis of echinomycin (1) was accomplished by featuring the late-stage construction of the thioacetal moiety via Pummerer rearrangement and simultaneous cyclization, as well as two-directional elongation of the peptide chains to construct a C2-symmetrical bicyclic octadecadepsi­peptide bridged with a sulfide linkage. This strategy can be applicable to a variety of echinomycin analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…To compare the toxicities of the new analogues to pancreatic cancer cells with the toxicity of 1 side by side, their activity against SW620 cells and MIA PaCa-2 cells is also shown in Table 1 . Similar to a previous investigation with MIA PaCa-2 cells 20 , 2 retained its potent toxicity to SW620 cells with an IC 50 value of 26 nM although a tenfold reduction in the activity was observed. Analogue 3 , which has 3-hydroxyquinoline chromophores, exhibited cytotoxicity equipotent to that of 1 (2.5 nM for 1 vs. 0.85 nM for 3 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…To compare the toxicities of the new analogues to pancreatic cancer cells with the toxicity of 1 side by side, their activity against SW620 cells and MIA PaCa-2 cells is also shown in Table 1 . Similar to a previous investigation with MIA PaCa-2 cells 20 , 2 retained its potent toxicity to SW620 cells with an IC 50 value of 26 nM although a tenfold reduction in the activity was observed. Analogue 3 , which has 3-hydroxyquinoline chromophores, exhibited cytotoxicity equipotent to that of 1 (2.5 nM for 1 vs. 0.85 nM for 3 ).…”
Section: Resultssupporting
confidence: 85%
“…It has been suggested that 1 is still a promising anticancer drug lead compound because of its ability to alter the clinical protocol. We accomplished the first total synthesis of 1 by constructing the characteristic thioacetal moiety via a Pummerer rearrangement of 2 in the late stage of the synthesis 20 . A brief structure–activity relationship study revealed that 2 reduces but still retains the toxicity of 1 to human pancreatic cancer MIA PaCa-2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…strains were reported to afford 2.5 mg/L (Jayasuriya et al, 2005 ) and 10 mg/L (Park et al, 1998 ) of echinomycin, respectively. The first total chemical synthesis of echinomycin was accomplished by Kojima et al ( 2020 ). As its chemical synthesis is low yield, process complicated, environmentally unfriendly, and has a lot of byproducts that are difficult to separate, new natural sources of echinomycin would have latent applied value.…”
Section: Discussionmentioning
confidence: 99%
“…In the total synthesis of echinomycin, isolated from Streptomyces echinatus , macrolactamization of the symmetrical peptide 15 was accomplished at the two places to give the cyclized product 16 (Scheme 5b). 15 High dilution conditions are usually required to avoid intermolecular coupling such as dimerization. Quite a superior yield was achieved in the macrolactamization of the acyclic precursor 17c , obtained from 17a via 17b , giving the 32-membered cyclic depsipeptide 18 (Scheme 5c).…”
Section: Amides and Lactams Synthesismentioning
confidence: 99%